2017
DOI: 10.1080/01434632.2016.1268146
|View full text |Cite
|
Sign up to set email alerts
|

The teaching of Chinese as a second or foreign language: a systematic review of the literature 2005–2015

Abstract: This paper reports the results of a review of research articles on the teaching of Chinese as a second or foreign language published in four leading mainland Chinese journals during the years 2005-2015. The review found that Chinese language researchers are exploring a wide array of issues including language policy and planning, language learning and use, language pedagogy, teacher development and language testing. These studies report the efforts that Chinese language researchers and teachers have made to mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 14 publications
2
79
0
Order By: Relevance
“…However, a few studies have surveyed literature on CFL to shed light on common areas of interest. For example, Ma et al (2017) conducted a literature review and found that related research focused on language policy and planning, language learning and use, language pedagogy, teacher development, and language testing.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a few studies have surveyed literature on CFL to shed light on common areas of interest. For example, Ma et al (2017) conducted a literature review and found that related research focused on language policy and planning, language learning and use, language pedagogy, teacher development, and language testing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, studying CFL before implantation is a must to avoid possible challenges. Ma, Gong, Gao, and Xiang (2017) and Gong, Lyu, and Gao (2018) believed that most previous research was focused on criticisms related to the teaching of Chinese by Confucius Institutes, which represent the Chinese government and seek to disseminate Chinese language and culture (Larsson, 2008). Regardless of the validity of these criticisms and concerns, which mostly focused on finance, academic viability, legal issues, relations, politics, and ideological resistance and attitudes, studying these challenges would save much time and effort for all involved.…”
Section: Introductionmentioning
confidence: 99%
“…Non-empirical studies usually stay at the level of opinion, a summary of personal experience, speculation or pure theoretical discussion and quantitative research is mainly used to examine the relationship between variables. Li's findings suggest a pressing need to further investigate Chinese character education for international students by using a more balanced and in-depth integration of positivist and interpretivist paradigms (Gao, Li, & Lü, 2001;Ma, Gong, Gao, & Xiang, 2017).…”
Section: Introducing the Special Issuementioning
confidence: 99%
“…Previous studies have analysed possible reasons for the challenges experienced by beginner learners in less commonly taught languages such as Chinese. First, there is the divergence of the language from European languages in terms of its orthographic system (Everson, 1998), the lack of vocabulary overlap between Chinese and European languages (Starr, 2009), and its tonal character (Ma, Gong, Gao, & Xiang, 2017). Second, there is a mismatch between learners' expectations and reality concerning how much effort is required for certain achievements (Wen, 1997).…”
Section: Research On Cflmentioning
confidence: 99%
“…Since much of the research is conducted by Chinese scholars and published in Chinese journals (Ma et al, 2017), research on critical issues in CFL in China published in English remains sparse. In their systematic review, the authors outline the increase of research interest in pedagogical innovation to provide tailored instructional approaches to help CFL learners manage the difficult target language (Ma et al, 2017). Recent literature on key pedagogical issues concerning language proficiency, enhancement of one of the four language skills, language-character integration vs. separation, and teaching materials development are included in this review.…”
Section: Cfl In Chinamentioning
confidence: 99%